Arrhythmogenic calmodulin E105A mutation alters cardiac RyR2 regulation leading to cardiac dysfunction in zebrafish. Issue 1 (2nd April 2019) - Da'as, Sahar I.; Thanassoulas, Angelos; Calver, Brian L.; Beck, Konrad; Salem, Rola; Saleh, Alaaeldin; Kontogianni, Iris; Al‐Maraghi, Ali; Nasrallah, Gheyath K.; Safieh‐Garabedian, Bared; Toft, Egon; Nounesis, George; et al.
Abstract: Calmodulin (CaM) is a universal calcium (Ca 2+ )‐binding messenger that regulates many vital cellular events. In cardiac muscle, CaM associates with ryanodine receptor 2 (RyR2) and regulates excitation–contraction coupling. Mutations in human genes CALM1, CALM2, and CALM3 have been associated with life‐threatening heart disorders, such as long QT syndrome (LQTS) and catecholaminergic polymorphic ventricular tachycardia. A novel de novo LQTS‐associated missense CaM mutation (E105A) was recently identified in a 6‐year‐old boy, who experienced an aborted first episode of cardiac arrest. Herein, we report the first molecular characterization of the CaM E105A mutation. Expression of the CaM E105A mutant in zebrafish embryos resulted in cardiac arrhythmia and increased heart rate, suggestive of ventricular tachycardia. In vitro biophysical and biochemical analysis revealed that E105A confers a deleterious effect on protein stability and a reduced Ca 2+ ‐binding affinity due to loss of cooperativity. Finally, the CaM E105A mutation resulted in reduced CaM–RyR2 interaction and defective modulation of ryanodine binding. Our findings suggest that the CaM E105A mutation dysregulates normal cardiac function by a complex mechanism involving alterations in both CaM–Ca 2+ and CaM–RyR2 interactions. Abstract : A novel de novo long QT syndrome–associated missense calmodulin (CaM) mutation E105A was recently identified in a 6‐year‐old boy, who experienced an aborted first episode of cardiac arrest. Our study reports the first in vivo and in vitro molecular characterization of the CaM E105A mutation. Our findings suggest that the CaM E105A mutation dysregulates normal cardiac function in zebrafish by a complex mechanism involving alterations in both CaM–Ca 2+ and CaM–ryanodine receptor 2 interactions.